Voicing sentiments of resilience: A corpus approach to 1980s conscious rappers in South Africa - Pedro Álvarez-Mosquera (AOSIS, 2021)
The study of people’s response to adversity acquires substantially different connotations in the South African context because of the heavy legacy of apartheid. This article explores the construction of the notion of resilience through the oral narrative production of the most prominent conscious rappers that emerged in the 1980s in South Africa, namely Prophets of Da City and Black Noise. By means of a corpus approach, our analysis with AntConc revealed that resilience is intrinsically connected to the historical sociopolitical struggle of the black group. In building this notion, results show how the parallel emergence of an oppressive other, the white group, plays a fundamental role. Relevant to our study, the affirmation of their black identity appears to act as an effective way of underpinning their possibility of resurgence. Furthermore, the objective analysis of rappers’ linguistic choices in their lyrics underlines their strategic use of personal pronouns, ethnic labels and other contextual-loaded terms whilst conveying their messages and communicating with their audience. These results both demonstrate the contribution of rap music in construction of a specific notion of resilience and highlight the effectiveness of this methodological approach, opening the floor to comparative studies.